A green tea polyphenol epigallocatechin-3-gallate enhances neuroregeneration after spinal cord injury by altering levels of inflammatory cytokines. (November 2017) - Machova Urdzikova, Lucia; Ruzicka, Jiri; Karova, Kristyna; Kloudova, Anna; Svobodova, Barbora; Amin, Anubhav; Dubisova, Jana; Schmidt, Meic; Kubinova, Sarka; Jhanwar-Uniyal, Meena; Jendelova, Pavla
Abstract: Spinal cord injury (SCI) is a debilitating condition which is characterized by an extended secondary injury due to the presence of inflammatory local milieu. Epigallocatechin gallate (EGCG) appears to possess strong neuroprotective properties. Here, we evaluated the beneficial effect of EGCG on recovery from SCI. Male Wistar rats were given either EGCG or saline directly to the injured spinal cord and thereafter a daily IP injection. Behavior recovery was monitored by BBB, plantar, rotarod and flat-beam tests. The levels of inflammatory cytokines were determined on days 1, 3, 7, 10 and 14 after SCI. Additionally, NF-κB pathway activity was evaluated. The results demonstrated that EGCG-treated rats displayed a superior behavioral performance in a flat beam test, higher axonal sprouting and positive remodelation of glial scar. Cytokine analysis revealed a reduction in IL-6, IL2, MIP1α and RANTES levels on days 1 and 3, and an upregulation of IL-4, IL-12p70 and TNFα 1 day following SCI in EGCG-treated rats. Treatment with EGCG was effective in decreasing the nuclear translocation of subunit p65 (RelA) of the NF-κB dimer, and therefore canonical NF-κB pathway attenuation. A significant increase in the gene expression of growth factors (FGF2 and VEGF), was noted in the spinal cord of EGCG-treated rats. Further, EGCG influenced expression of M1 and M2 macrophage markers. Our results have demonstrated a therapeutic value of EGCG in SCI, as observed by better behavioral performance measured by flat beam test, modulation of inflammatory cytokines and induction of higher axonal sprouting. Highlights: EGCG improved fuctional outcome, increased axonal sprouting and remodelate glial scar in rats with spinal cord injury. EGCG treatment attenuated canonical NFkB pathway. EGCG treatment increased the gene expression of growth factors (FGF2 and VEGF) in injured spinal cord.